Lip Repositioning Surgery: A Newer Paradigm in Periodontal Aesthetics - Humagain, Manoj; Dawadi, Asmita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Periodontal plastic or aesthetic surgery by its definition comprises of surgical procedures performed to correct or eliminate anatomic, developmental or traumatic deformities of the gingiva or oral mucosa. ‘Perfect smile’ has been the common desire of many people in this era. Smile has significant role in the expression, appearance and in the development of self-esteem. Excessive gingival display, which is commonly termed as ‘gummy smile’ will adversely affects smile aesthetics and is therefore undesirable to many people. It is one of the several developmental or acquired deformities and conditions that manifest in the periodontium. Different literature reveals common consensus on considering gingival display of greater than 3 mm is gummy smile and is unaesthetic. Lip repositioning surgery has been establishing as a promising less invasive alternative treatment modality in aesthetic rehabilitation for the cases of excessive gingival display. Perseverance and application of such technique shall provide many more a horizon to this young but highly imaginative and creative technique in periodontal therapy to charter.